Pengaturan dan Pengelolaan Aset Tanah Negara dengan Lahirnya Badan Bank Tanah - Della Edwinar; Lukman Hakim; Sirajuddin Sirajuddin (Legal Spirit, 2023)
The Job Creation Law has a major influence with the issuance of Government Regulation No. 64 of 2021 on the Land Bank Agency. Through the Perpres, it is hoped that it can create arrangements and management of state land assets, especially abandoned land, so that it can be utilized for the prosperity of the people. Based on this description, this study aims to determine and analyze the regulation and management of state land assets before the existence of Government Regulation Number 64 of 2021 concerning the Land Bank Agency, to determine and analyze the factors that become obstacles in the regulation and management of state land assets so that a Land Bank Agency is needed. and to know and analyze the legal construction of the regulation and management of the Land Bank Agency in the future. The type of research used is normative juridical research using a statutory approach and concept approach. The research results obtained are: First, the regulation and management of state land assets before the Perpres of the Land Bank Agency was carried out by BPN. Second, the regulation and management of state land assets before the existence of Government Regulation Number 64 of 2021 concerning the Land Bank Agency, the management is still carried out by the National Land Agency (BPN), and the legal construction of the regulation and management of state land assets in the future is a way to fill the void of land bank regulations through principles and values in society.